Dampak Keluarga Suami Di Perantauan Terhadap Keadaan Rumah Tangganya Dalam Tinjauan Hukum Keluarga Islam (Studi Kasus Di Dusun Rujing, Desa Sungaiteluk, Kecamatan Sangkapura Bawean) - Muridah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Every individual longs for a harmonious household life. However, creating an ideal household is not easy, especially for families separated by distance because one party has migrated. This study aims to analyze the condition of households left by husbands who have migrated in Rujing Hamlet, Sungaiteluk Village, Sangkapura District, and the role of husbands in fulfilling their responsibilities as heads of families according to the perspective of Islamic Family Law. This study examines two main aspects, namely the condition of families left by husbands who have migrated, and the role of husbands in maintaining their responsibilities despite being separated by distance. The results of the study show three main conditions experienced by families who have migrated: 1. The psychological condition of the wife who feels lonely, tired, and has to replace the father figure, 2. The sociological condition where the wife feels she lives alone without a companion in the family and society, and 3. The family's economic condition tends to be better. The study was conducted in Rujing Hamlet, Sungaiteluk Village, Sangkapura District, involving five main informants. The results of the interviews showed that the husband's departure to migrate had a significant impact on the wife, children, and the family's economic condition. Wives face various challenges, such as loneliness, the burden of housework, and having to take care of children alone. However, the existence of communication through technology such as video calls can ease the longing a little. The impact on children varies, from remaining enthusiastic about learning to needing an approach to strengthen relationships with fathers through long-distance communication. From an economic perspective, most families experience improved welfare after their husbands migrate, even though they have to sacrifice family togetherness. From the perspective of Islamic Family Law, the husband's responsibility as head of the family is maintained by implementing the principles of honesty, openness, mutual trust, and good communication. This commitment is the main key to maintaining household harmony even though they are separated by distance.